ANALISIS FUNDAMENTAL PENGAMBILAN KEPUTUSAN INVESTASI PADA SAHAM PT. ASTRA INTERNASIONAL TBK PERIODE 2021-2025 - Vira Novitasari; Teuku Ardian Maulana; Army Juliansyah; Satria Wahyu Hidayat; Alya Fitri Damayanti; Ismail Zulhaj Tuasikal (Jurnal Ilmiah Akuntansi, 2026)
This study aims to analyze fundamental performance as a basis for investment decision-making regarding the shares of PT Astra International Tbk. The following study uses a descriptive study design using a quantitative approach., using secondary data obtained through the company’s financial statements also published stock prices. The data collection techniques used are documentation and literature review methods, while data analysis employs quantitative descriptive analysis with a fundamental analysis approach through financial ratios, including Return on Equity (ROE), Earnings Per Share (EPS), Debt to Equity Ratio (DER), Price Earnings Ratio (PER) dan Price to Book Value (PBV). The results of the study indicate that the company’s fundamental performance is generally in good condition, characterized by relatively high profitability levels, a sound capital structure, and the the company's capacity to provide profits to investors. Meanwhile, the company’s stock tends to trade at a relatively low level in the market compared to its fundamental value, indicating potential undervaluation. Based on these results, fundamental analysis can serve as an effective basis for investment decision-making, where the company’s stock is deemed worthy of consideration as an investment option, particularly for long-term investors.